PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA PRODUCTORA Y COMERCIALIZADORA DE PULPA DE TOMATE DE ÀRBOL, EMPACADO AL VACÍO, PARA EL CANTÓN LOJA - Cabrera Ruíz, Santiago Fernando (2016)
This research is performed in the canton Loja in order to improve the economic situation of our city and canton and in turn improve the productivity of the same. Regarding the development of the project entitled: "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A producer and marketer tomato pulp TREE, VACUUM PACKED FOR THE Loja Canton". For the study of research materials such as office supplies and computer equipment were used, the methods used were inductive method which helped to collect information through market research; deductive method allowed to obtain valid conclusions determining whether it is viable or not the creation of the project Market research was conducted to determine the conditions of supply and demand in the market of Canton Loja, market variables which help us in the formulation of the surveys led us to the lifting of the information was analyzed to in thus continuing the project, and then statistical sampling taking into account the number of families in the canton of Loja is 240 374 inhabitants in 2015 and 60 094 families gave a total of 397 surveys were applied in the canton Loja was made, in order to meet the demand that will have the product on the market. The technical study allowed us to analyze the factors of optimal location of the company and this was located in the canton Loja in Loja Under Zalapa neighborhood, it is considered a sector that provides systems for access roads to the north-south direction and vice versa thus allowing easy 6 transportation of inputs and the distribution of the product; and, to establish the installed annual capacity is 58,400 liters, all to the ten-year life of the project. Capacity utilization of the project for the first year is 37,488 also established The company will have adequate infrastructure and requirements necessary for its operation, ie the raw material, labor and all the instrumentation necessary for the development and marketing of the product, at the right price to established market segment. It is to develop marketing activities tomato pulp tree: administrative studio where the trade name of the company was established was analyzed. This for-profit organization, will be a limited liability company and named "S & R" Cia. Ltda. In the financial study the initial investment of $ 37,579.57 which is the 62.75% financing with equity capital and 37.25% with foreign capital financed by the National Development Bank with an interest rate of 15% was determined budget operation for the first year 92522.34, sales income of $ 108,715.20. As for the financial evaluation the project is reflected in the positive financial indicators with a projected ten years 141,756.47 Net Present Value is obtained; Internal Rate of Return of 42.12%; Cost benefit ratio is 1.23 for every dollar invested the company earns 23 cents; Capital recovery period is 2 years and 6 months; Sensitivity analysis indicates that the project supports an increase in cost of 9.05% for a total of 0.98% and the sensitivity analysis in the decrease in revenues of 7.50% for a total of 7 0.99% ; so the project is feasible, the conclusions and recommendations so determined, accompanied by the bibliography consulted with their respective annexes.